PENGARUH PEMANFAATAN PERPUSTAKAAN UNTAN SEBAGAI SUMBER BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA FKIP ANGKATAN 2016 - Wirananda, Adhitia; Aminuyati, Aminuyati; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstrak Thesis "The Influence of Library Utilization as a Learning Source for Student Learning Achievement in 2016 FKIP". The problem of research is the influence of the use of the library on student learning achievement. sub-problem of research on how students use the library, how is the student's learning achievement, is there any influence of using the library on learning achievement, how much influence does the library use on learning achievement. students have used the library. The variables in this study are independent variables (X) library utilization and dependent variable (Y) learning achievement. Descriptive method research method, a form of relationship study. The population is 78 students. data collection of indirect communication techniques, namely questionnaires and documentation. Data processing techniques use simple linear regression. The results of the study are the positive influence of the use of the library on learning achievement. Large contribution of Â is 0.089. Stating that the utilization of untan library on learning achievement is 8.9%. While the rest is influenced by other variables.Â Keywords: Library Utilization, Learning Achievement